2012
DOI: 10.4103/0301-4738.91344
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Framingham cardiovascular risk scores in subjects with diabetes and their correlation with diabetic retinopathy

Abstract: Aim:To study the Framingham cardiovascular risk assessment scores in subjects with diabetes and their association with diabetic retinopathy in subjects with diabetes.Materials and Methods:In this population-based prospective study, subjects with diabetes were recruited (n=1248; age ≥40 years). The Framingham cardiovascular risk scores were calculated for 1248 subjects with type 2 diabetes. The scores were classified as high risk (>10%), and low risk (<10%).Results:Out of the 1248 subjects, 830 (66.5%) patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 14 publications
0
10
0
1
Order By: Relevance
“…In the MDRS 24-month cohort study, lower hemoglobin was associated with the presence of STDR at baseline (previously reported 14 ) but not with the progression of DR. Cross-sectional (but not cohort) studies have demonstrated an association between the presence of DR and anemia in India32, 33, 34 and China 35 . Potential confounders of the association between hemoglobin and retinopathy are socioeconomic and nutritional status and decreased erythropoietin production due to diabetic nephropathy.…”
Section: Discussionmentioning
confidence: 99%
“…In the MDRS 24-month cohort study, lower hemoglobin was associated with the presence of STDR at baseline (previously reported 14 ) but not with the progression of DR. Cross-sectional (but not cohort) studies have demonstrated an association between the presence of DR and anemia in India32, 33, 34 and China 35 . Potential confounders of the association between hemoglobin and retinopathy are socioeconomic and nutritional status and decreased erythropoietin production due to diabetic nephropathy.…”
Section: Discussionmentioning
confidence: 99%
“…In not stratifying HDL-C and confirmed by other authors [1]- [11] [31]- [41], traditional cardiovascular disease (CVD) risk factors such as smoking status, MS, high 10-year Framingham risk, insulin therapy, low intake of vegetables (Fumbwa leaves, beans), low education, low SES, elevated ApoB, HbA1c no control, and FPG no control were individually and significantly associated with DR in all T2DM patients.…”
Section: P-valuementioning
confidence: 79%
“…These paradoxical associations of a quantitative HDL-C trait could be dependent on genetic, ethnic, minority, and environmental (lifestyle changes: migration, urbanization, westernization, inappropriate diet, smoking, exaggerated physical activity, excessive alcohol intake) factors [41]- [52]. There are positive association between total cholesterol, the deficiency in cholesterol ester transfer protein (CETP), DR, poor control of HbA1c, insulin therapy, and increasing HDL-C levels in diabetic Africans [38] [46]- [48] people from developed countries [49]- [52] and Asians [8].…”
Section: Independent Determinants Of Dr By Stratifying Hdl-c Levelsmentioning
confidence: 99%
“…Thus not all raised total serum HDLC are equally anti-atherogenic emphasizing HDLC particle composition rather than total HDLC, as an important determinant of its specific functional property (and role) as agreed by the expert clinical lipidologists. [1] Moreover, the inverse correlation between serum HDLC concentration and risk of CHD (Coronary Heart Disease) and decreased cardiovascular (CVD) risk with increasing HDLC levels have been known for years, particularly South Asians are not only notorious to have lower HDLC levels but also have a higher concentration of small, decreased-cardio-protective HDL particles. [34]…”
mentioning
confidence: 99%